An 8-gene mRNA expression profile in circulating tumor cells predicts response to aromatase inhibitors in metastatic breast cancer patients. Issue 1 (December 2016) - Reijm, Esther; Sieuwerts, Anieta; Smid, Marcel; Vries, Joan; Mostert, Bianca; Onstenk, Wendy; Peeters, Dieter; Dirix, Luc; Seynaeve, Caroline; Jager, Agnes; de Jongh, Felix; Hamberg, Paul; et al.
Abstract Background Molecular characterization of circulating tumor cells (CTC) is promising for personalized medicine. We aimed to identify a CTC gene expression profile predicting outcome to first-line aromatase inhibitors in metastatic breast cancer (MBC) patients.Methods: CTCs were isolated from 78 MBC patients before treatment start. mRNA expression levels of 96 genes were measured by quantitative reverse transcriptase polymerase chain reaction. After applying predefined exclusion criteria based on lack of sufficient RNA quality and/or quantity, the data from 45 patients were used to construct a gene expression profile to predict poor responding patients, defined as disease progression or death <9 months, by a leave-one-out cross validation. Results Of the 45 patients, 19 were clinically classified as poor responders. To identify them, the 75 % most variable genes were used to select genes differentially expressed between good and poor responders. An 8-gene CTC predictor was significantly associated with outcome (Hazard Ratio [HR] 4.40, 95 % Confidence Interval [CI]: 2.17–8.92, P  < 0.001). This predictor identified poor responding patients with a sensitivity of 63 % and a positive predictive value of 75 %, while good responding patients were correctly predicted in 85 % of the cases. In multivariate Cox regression analysis, including CTC count at baseline, the 8-gene CTC predictor was the only factor independently associated with outcome (HR 4.59 [95 % CI: 2.11–9.56], P  < 0.001). This 8-gene signature was not associated with outcome in a group of 71 MBC patients treated with systemic treatments other than AI. Conclusions An 8-gene CTC predictor was identified which discriminates good and poor outcome to first-line aromatase inhibitors in MBC patients. Although results need to be validated, this study underscores the potential of molecular characterization of CTCs.